گل رعنا مرتبہ مالک رام(۱۹۷۰ء) کا تجزیاتی مطالعہ - Baloch, Ramzan (Tabeer e Nau, 2025)
Ram is a famous researcher, critic and editor on Ghalib's works. In this regard Zikr-e-Ghalib, Talamzae-Ghalib, Fasana-e-Ghalib and Tehqiqi Mazameen are considered his masterpieces. While Diwaan-e-Ghalib, Gul-e-Ra’na, Sabad Cheen, Dastanbo, Khatoot-e-Ghalib, Ayar-e-Ghalib, Yadgar-e-Ghalib and Tehreer (Ghalib No) are his significant ventures. Malik Ram Compiled Gul-e-Ra’na in 1970 and then edited it. This is based upon his personal Transcript, Nuskha-e-Lahore and derived different material from Diwaan-e-Ghalib's editions and made it a variorum edition. Gul-e-Ra’na is a critical edition.